Protective Effect of Minocycline Against Ketamine-Induced Injury in Neural Stem Cell: Involvement of PI3K/Akt and Gsk-3 Beta Pathway - Lu, Yang; Lei, Shan; Wang, Ning; Lu, Pan; Li, Weisong; Zheng, Juan; Giri, Praveen K.; Lu, Haixia; Chen, Xinlin; Zuo, Zhiyi; Liu, Yong; Zhang, Pengbo (Frontiers in Molecular Neuroscience, 2016)
Abstract It has been suggested that ketamine cause injury during developing brain. Minocycline could prevent neuronal cell death through the activation of cell survival signals and the inhibition of apoptotic signals in models of neurodegenerative diseases. Here we investigated the protective effect of minocycline against ketamine-induced injury in neural stem cell(NSC) from neonatal rat. Ketamine (100μM/L) significantly inhibited NSC proliferation, promoted their differentiation into astrocytes and suppressed neuronal differentiation of NSCs. Moreover, the apoptotic level was increased following ketamine exposure. Minocycline pretreatment greatly enhanced cell viability, decreased caspase-3-like activity, even reversed the differentiation changes caused by ketamine. To elucidate a possible mechanism of minocycline’ neuroprotective effect, we investigated the phosphoinositide3- kinase pathway using LY294002, a specific PI3K inhibitor. Immunoblotting revealed that minocycline enhanced the phosphorylation/activation of Akt and phosphorylation/inactivation of glycogen synthase kinase-3beta (Gsk-3β).Our results suggest that PI3K/Akt and Gsk-3β pathway are involved in the neuroprotective effect of minocycline.